2018
DOI: 10.3389/fendo.2018.00525
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol as an Endogenous ERRα Agonist: A New Perspective to Cancer Treatment

Abstract: The estrogen-related receptors (ERRs) are important members of nuclear receptors which contain three isoforms (α, β, and γ). ERRα is the best-characterized isoform expressed mainly in high-energy demanding tissues where it preferentially works in association with the peroxisome proliferator-activated receptor-γ co-activator 1α (PGC-1α) and PGC-1β. ERRα together with its cofactors modulates cellular metabolism, supports the growth of rapidly dividing cells, directs metabolic programs required for cell different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 97 publications
3
33
0
Order By: Relevance
“…All the cohort and case control studies which focused on the relationship of bisphosphonates and breast cancer did not separate statins use from control group either [15][16][17][18][19][20][21][22][23]. In our study, statins showed similar breast cancer protective effect as bisphosphonates in consistence with published preclinical research [11][12][13]. It is possible that the comparable breast cancer protective effect of bisphosphonates or statins might be masked when the control group has comedication of either of these two drugs.…”
Section: Comparison Of Our Results With Other Studiessupporting
confidence: 65%
See 1 more Smart Citation
“…All the cohort and case control studies which focused on the relationship of bisphosphonates and breast cancer did not separate statins use from control group either [15][16][17][18][19][20][21][22][23]. In our study, statins showed similar breast cancer protective effect as bisphosphonates in consistence with published preclinical research [11][12][13]. It is possible that the comparable breast cancer protective effect of bisphosphonates or statins might be masked when the control group has comedication of either of these two drugs.…”
Section: Comparison Of Our Results With Other Studiessupporting
confidence: 65%
“…ERRα plays roles in osteoporosis and breast cancer development. ERRα transcriptional activity is enhanced by cholesterol and suppressed by statins and bisphosphonates [11][12]. Meanwhile, the epigenetic impacts of statin and bisphosphonates on DNA methylation, histone deacetylation and microRNAs occurring in normal cells could be both cancer preventing and promoting [13].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggest that endogenous cholesterols may be potential ESRRA ligands [31,53]. Moreover, PPARGC1A increases cholesterol-ESRRA interaction and cholesterol stabilizes the ESRRA-PPARGC1A complex [53,54].…”
Section: Identification Of Potential Esrra Ligandsmentioning
confidence: 99%
“…Similarly, increasing the expression of peroxisome proliferator-activated receptor gamma coactivator 1 alpha (PPARGC1A), the protein ligand of ESRRA, increases energy expenditure and reduces obesity [23]. So far, most previous studies of ESRR actions have focused on its role in cancer progression and this topic has been reviewed elsewhere [24][25][26][27][28][29][30][31][32][33][34][35]. There have also been a few studies on its roles in bone and muscle differentiation [36][37][38], trauma/shock [39], and infection [40].…”
Section: Introductionmentioning
confidence: 99%
“…As stated above, cholesterol can also act as a functional and endogenous agonist of , which has important roles in cancer, fatty acid metabolism, skeletal homeostasis, as well as mitochondria biogenesis and function (17,18). In addition to the above processes, cholesterol is a major regulator of lipid organization, being responsible for the close packing of acyl chains of phospholipids, promoting phase separation and stabilizing the formation of cholesterol and sphingolipid-rich membrane microdomains known as lipid rafts or membrane rafts (19,20), which constitute centers of organization for signal transduction and trafficking in normal and cancer cells (21-23).…”
Section: Pleiotropic Actions Of Cholesterol In Cell Physiology and Mamentioning
confidence: 99%